Client, Industry and Country Factors Affecting Choice of Big N Industry Expert Auditors - Ettredge, Michael (Institutional Knowledge at Singapore Management University, 2005)
This study investigates client choice of industry specialist auditors from among the Big N (Big 4 or 5) in an international (non-U.S.) setting. We investigate client-specific, industry-level and country-level factors hypothesized to enhance or decrease Big N clients' demand for industry expertise. Using data for 29 countries and 14 broad industries from 1993-2005, we find that international client choice of industry specialist Big N auditors is positively associated with client size, client growth opportunities, and client capital intensity. The choice of industry specialists from among the Big N is more prevalent in countries where levels of investor protection, quality of financial reporting environment, and national economic development are higher. Clients belonging to regulated industries tend to select industry specialists.